2015
DOI: 10.1111/corg.12125
|View full text |Cite
|
Sign up to set email alerts
|

Weathering the Storm: Family Ownership, Governance, and Performance Through the Financial and Economic Crisis

Abstract: Manuscript Type: Empirical\ud Research Question/Issue: Considering the recent financial and economic crisis as a unique exogenous shock, our study investigates\ud the financial performance of family-controlled firms in “steady-state” conditions as opposed to situations of severe economic\ud distress. In addition, we focus our attention within family firms in order to tease out the leadership (family or non-family\ud CEO) and family ownership (family ownership concentration or dispersion) conditions that allow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
144
2
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 193 publications
(181 citation statements)
references
References 124 publications
8
144
2
6
Order By: Relevance
“…In this way, our findings also contribute to the recent debate on "mixed gambles" (Gomez-Mejia et al, 2014;Martin, Gomez-Mejia, & Wiseman, 2013), suggesting that predictions regarding the behavior of family managers as riskaverse or risk-prone should be contextualized in a correct alignment of checks and balances between FMs and NFMs. Recent evidence shows indeed the importance of the context to understand SEW influences over family firms' behaviors and financial performance outcomes (Minichilli, Brogi, & Calabrò, 2015). Finally, our study also calls for a tighter integration between family business and traditional management and strategic leadership literatures in explaining how the composition and characteristics of family and non-family actors at multiple levels of ownership, governance, and leadership inside the family firm influence its strategic choices and financial performance.…”
Section: Theoretical Implicationsmentioning
confidence: 60%
“…In this way, our findings also contribute to the recent debate on "mixed gambles" (Gomez-Mejia et al, 2014;Martin, Gomez-Mejia, & Wiseman, 2013), suggesting that predictions regarding the behavior of family managers as riskaverse or risk-prone should be contextualized in a correct alignment of checks and balances between FMs and NFMs. Recent evidence shows indeed the importance of the context to understand SEW influences over family firms' behaviors and financial performance outcomes (Minichilli, Brogi, & Calabrò, 2015). Finally, our study also calls for a tighter integration between family business and traditional management and strategic leadership literatures in explaining how the composition and characteristics of family and non-family actors at multiple levels of ownership, governance, and leadership inside the family firm influence its strategic choices and financial performance.…”
Section: Theoretical Implicationsmentioning
confidence: 60%
“…Based on the principal-principal agency theory framework (Young, Peng, Ahlstrom, Bruton, & Jiang, 2008), our study attempts to shed light on the aforementioned research question by exploring how family blockholders affect firm behavior and expose firms to principal-principal problems (Boyd & Solarino, 2016). In principalprincipal conflicts, blockholders' interests and goals do not align with those of minority shareholders or other blockholders (e.g., Minichilli, Brogi, & Calabrò, 2016), increasing the likelihood of the expropriation of nonblockholders. In the context of family firms, goal discrepancy among shareholders is aggravated by the pursuit of goals other than economic wealth by owner families (Aparicio, Basco, Iturralde, & Maseda, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we also control for various corporate governance characteristics, including board size ( BOARD_SIZE ), board independence ( IND_BOARD ), the presence of an audit committee ( AUDIT_COMMIT ), CEO duality ( DUALITY ), and total external block ownership ( BLOCK_OWN ). It has been suggested that these corporate governance characteristics are associated with the effectiveness of monitoring functions and the financial reporting quality of a firm, and consequently have an impact on the firm's demand for high‐quality auditors (e.g., Beasley & Petroni, ; Cohen, Krishnamoorthy, & Wright, ; Grove, Patelli, Victoravich, & Xu, ; Ho & Kang, ; Klein, ; Minichilli, Brogi, & Calabrò, ).…”
Section: Research Methodoligymentioning
confidence: 99%